2020
DOI: 10.35808/ersj/1865
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Capabilities Revisited: Lessons from Logistics

Abstract: Purpose: The identification of the premises concerning shaping and developing logistics capabilities towards firm dynamic capabilities. Design/Methodology/Approach: The article uses an analytical approach based on the results of previous studies. Findings: Logistics capabilities can be perceived and implemented as the strategic capabilities of a firm. As a result, logistics capabilities may aspire to become the dynamic capabilities of a firm. Practical Implications: Logistics capabilities aspiring to become th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Dynamic capability has dominated business literature as a leveraging factor against negative adversaries (Ugboego et al 2022;Akpan et al 2021;Ezenwakwelu et al 2021;Matwiejczuk et al 2020;Sukaris et al 2019;Ofoegbu and Onuoha 2018). From the word "dynamic", it could be deduced to mean an unstable measure or something that changes overtime.…”
Section: Dynamic Capabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic capability has dominated business literature as a leveraging factor against negative adversaries (Ugboego et al 2022;Akpan et al 2021;Ezenwakwelu et al 2021;Matwiejczuk et al 2020;Sukaris et al 2019;Ofoegbu and Onuoha 2018). From the word "dynamic", it could be deduced to mean an unstable measure or something that changes overtime.…”
Section: Dynamic Capabilitymentioning
confidence: 99%
“…Jhony et al (2020) alluded that in a dynamic business environment, businesses must strive to build a strong dynamic capability so that when turbulence arises, they would be able to withstand it. Research has shown that dynamic capability helps organisations to sense an environmental crisis and plan how to reconfigure its structures (Cyfert et al 2021;Matwiejczuk et al 2020;Apriza and Utami 2018). Akpan et al (2021) added that after sensing the environmental forces that disrupted the organisation's operation, the next course of action is for managers to reconfigure the affected areas.…”
Section: Introductionmentioning
confidence: 99%